Characterization of a Standardized Ex-vivo Porcine Model to Assess Short Term Intraocular Pressure Changes and Trabecular Meshwork Vitality After Pars Plana Vitrectomy with Different Silicone Oil and BSS Tamponades. (3rd August 2017) - Ebner, Martina; Mariacher, Siegfried; Hurst, José; Szurman, Peter; Schnichels, Sven; Spitzer, Martin S.; Januschowski, Kai
ABSTRACT: Purpose : The aim of this study was to characterize a standardized porcine ex-vivo testing system for intraocular pressure (IOP) monitoring after vitrectomy with different endotamponades. Methods : Twenty-four pig eyes, six per endotamponade group were obtained immediately postmortem. After pars plana vitrectomy, vitreous substitutes (silicone oil 1000 mPas, 2000 mPas, 5000 mPas, and Balanced Salt Solution (BSS)) were instillated and IOP was observed over 24-hours. Infusion pumps with Dulbecco's Modified Eagle Medium (DMEM) simulated a constant aqueous humor circulation. A histological examination of the trabecular meshwork with DAPI- and TUNEL-staining was performed to detect the amount of apoptotic cells. Results : TUNEL-assay showed a mean cell death rate of 3.78% (SD ± 1.46%) for silicone oil endotamponades compared to 5.05% (SD ± 2.18%) in BSS group. One-way ANOVA ( p = 0.425) showed no significant difference between both groups. Mean IOP in silicone oil endotamponades was 9.50 mmHg (SD ± 1.68 mmHg) at baseline, 13.23 mmHg (SD ± 0.79 mmHg) after 1 hour, 18.46 mmHg (SD ± 2.13 mmHg) after 12 hours and 15.51 mmHg (SD ± 2.82 mmHg) 24 hours after instillation. A comparison of all silicone oil groups (one-way ANOVA, Bonferroni post-hoc test, p = 0.269 to 1.000) didn't reveal significant differences in mean IOP. Conclusion : The standardized ex-vivo porcine model represents an effective alternative to the in-vivo testing in animals. Maintaining the trabecular and uveoscleral outflow pathway enables a pseudo in-vivo analysis.